Potato wound-healing tissues: A rich source of natural antioxidant molecules with potential for food preservation. (1st November 2016) - Dastmalchi, Keyvan; Wang, Isabel; Stark, Ruth E.
Highlights: ABTS + scavenging activity was assessed for potato wound periderm extracts. Activity monitored vs. time revealed fast- and slow-acting antioxidant fractions. The compositions of the most active fractions were analysed using LC–MS. The antioxidant compounds in the most active fractions were identified structurally. Abstract: The need for safe, effective preservatives is a prominent issue in the food and drug industries, reflecting demand for natural alternatives to synthetic chemicals viewed as harmful to consumers and the environment. Thus, this study determined the identities and scavenging capacities of antioxidant metabolites produced as a response to potato tuber wounding, using activity-guided fractionation of polar extracts from a Yukon Gold cultivar that had previously exhibited exceptionally high radical-scavenging activity. Activity-guided fractionation using the ABTS + radical scavenging assay and LC–MS with TOF-MS for compositional analysis of the most potent antioxidant fractions yielded identification of nine constituents: coumaroylputrescine; feruloylquinic acid; isoferuloylputrescine; ferulic acid; 22, 25-dimethoxy-3-[[2, 3, 4-tri- O -methyl-6-O-(2, 3, 4, 6-tetra- O -methyl-β-d -glucopyranosyl)-β-d -glucopyranosyl]oxy]-(3β)-lanost-9(11)-en-24-one; 4-(2 Z )-2-decen-1-yl-5-[1-(4-hydroxyphenyl)decyl]-1, 2-benzenediol; 8-[(2 E )-3, 7-dimethyl-2, 6-octadien-1-yl]-5-hydroxy-2, 8-dimethyl-6-(3-methyl-2-buten-1-yl)-2 H -1-benzopyran-4, 7(3 H, 8 H )-dione; 3-[(2- O -β-d -glucopyranosyl-β-d -glucopyranosyl)oxy]-20-[(6- O -β-d -xylopyranosyl-β-d -glucopyranosyl)oxy]-dammar-24-en-19-al; (3β)-28-oxo-28-(phenylmethoxy)oleanan-3-yl 2- O -β-d -galactopyranosyl-3- O -(phenylmethyl)-, butyl ester β-d -glucopyranosiduronic acid. A positive correlation was observed between the scavenging activities and the polarities of the active fractions. The antioxidant capacities of the fractions were also characterised by monitoring the activity throughout a 45-minute assay period.